Analysis of Slow-Released Fertilisers as a Source of Microplastics - Vladimir Isakov; Elena Vlasova; Vladislav Forer; Jose Kenny; Sergey Lyulin (Land)
One of the main strategies for improving the efficiency of agricultural production is the use of fertilisers with slow or controlled release of nutrients, in which the granules of mineral fertilisers are covered with polymeric shells. The composition of the polymer coatings of mineral fertiliser granules with slow or controlled release of two widespread manufacturers and their ability to adsorb some heavy metal ions on their surface were examined in this study. It was found that the base polymers used to encapsulate the fertilisers studied are the co-polymer polyethylene–polyacrylic acid in the Brand A, and polyacrylamide, polyacrylic acid, and its esters in the Brand B fertiliser coating. The maximum adsorption rate of heavy metal ions on the surface of the polymer coatings with the rest of the mineral filler of Brand A and Brand B fertilisers was 54.64 and 28.90 mg/g for Cd(II) ions, 30.77 and 14.03 mg/g for Pb(II) ions, respectively. Therefore, the solution to the problem of increasing the efficiency of agricultural production through the use of fertilisers with slow or controlled release of nutrients leads to environmental pollution by microplastics remaining in the soil after fertiliser application, which are also capable of adsorbing from the soil various toxic pollutants.